Effect of Er:YAG laser radiation on pull-out fracture load of esthetic posts luted to root canal dentin with various resin cements - Horieh Moosavi; Farzaneh Ahrari; Maryam Zanjani (Wolters Kluwer Medknow Publications, 2021)
Background: This study investigated the influence of erbium-doped: yttrium aluminum garnet (Er:YAG) laser on the pull-out fracture load of fiber-reinforced composite (FRC) posts luted to dentin with different resin cements. Materials and Methods: In this in vitro experimental study, 90 premolars were endodontically treated. The post spaces were prepared, and the teeth were divided into three groups dependent on the cement applied for luting FRC posts: Group 1: An etch-and-rinse system, Group 2: A self-etch cement, and Group 3: A self-adhesive cement. After 6 months' storage and thermocycling, each group was divided into three subgroups (n = 10) according to the treatment applied for removing the posts; subgroup 1: Control, subgroup 2: Treatment with Er:YAG laser at 250 mJ, 20 Hz, and subgroup 3: Treatment by Er:YAG laser at 300 mJ, 10 Hz. The pull-out load was recorded in Newton. The data were analyzed by two-way ANOVA at P < 0.05. Results: The fracture load was significantly affected by the cementation group (P = 0.005) and treatment subgroup (P = 0.008). The pull-out load of self-etch cement was significantly greater than that of the self-adhesive and etch-and-rinse systems (P < 0.05). Treatment with Er:YAG laser caused a significant reduction in pull-out load of FRC posts (P < 0.05). Conclusion: The fracture load of fiber posts is influenced by the type of cement and treatment applied. Post removal would be less challenging when using a self-adhesive or conventional etch-and-rinse cement or using Er:YAG laser at the FRC-resin interface.